Bilateral mandibular block improves pain relief and morphine consumption in mandibular osteotomies: a prospective, randomized, double-blind, placebo-controlled clinical trial. Issue 4 (9th February 2021) - Bertuit, Marina; Rapido, Francesca; Ly, Habib; Vannucci, Charlotte; Ridolfo, Jérôme; Molinari, Nicolas; De Boutray, Marie; Galmiche, Sophie; Dadure, Christophe; Perrigault, Pierre-François; Capdevila, Xavier; Chanques, Gérald
Abstract : Background: The sensory innervation of the lower jaw mainly depends on the third root of the trigeminal nerve, the mandibular nerve (V3). The aim of this single-center, prospective, randomized, double-blind, placebo-controlled study was to evaluate the effectiveness of bilateral V3 block for postoperative analgesia management in mandibular osteotomies. Methods: 107 patients undergoing mandibular surgery (75 scheduled osteotomies and 32 mandible fractures) were randomized in two groups. A bilateral V3 block was performed in each group, either with ropivacaine 0.75% (block group, n=50) or with a placebo (placebo group, n=57). A postoperative multimodal analgesia was equally provided to both groups. The primary outcome was the cumulative morphine consumption at 24 hours. Secondary outcomes were the occurrence of severe pain and the incidence of postoperative nausea and vomiting (PONV) in the first 24 hours. Data were analyzed on an intention-to-treat basis. Results: The cumulative morphine consumption at 24 hours was significantly lower in the block group (median 8.0 mg (IQR 2.0–21.3) vs 12.0 mg (IQR 8.0–22.0), p= 0.03 ), as well as the incidence of severe pain during the 24 hours of follow-up (4.0% vs 22.8%, p<0.01). The mandibular block had no impact on the incidence of PONV. Conclusion: Bilateral V3 block for mandibular osteotomies is an effective opioid-sparing procedure. It provided better postoperative analgesia in the first 24 hours, and it did not affect PONV incidence. Trial registration number: NCT02618993 .